{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

HW08-problems

# HW08-problems - qerqez(anq78 HW08 berg(54595 This print-out...

This preview shows pages 1–3. Sign up to view the full content.

qerqez (anq78) – HW08 – berg – (54595) 1 This print-out should have 24 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0points Find the derivative of f when f ( x ) = x 3 x + 1 x . 1. f ( x ) = 2 x (3 x 2 + 1) 2 2. f ( x ) = - 2 x (3 x 2 + 1) 2 3. f ( x ) = 1 3 + 1 x 2 4. f ( x ) = 1 3 - 1 x 2 5. f ( x ) = 2 x 3 x 2 + 1 6. f ( x ) = - 2 x 3 x + 1 002 10.0points Find the derivative of f when f ( x ) = x ( x - 2) . 1. f ( x ) = 3 x - 2 2 x 2. f ( x ) = 3 x + 2 x x 3. f ( x ) = 3 x + 2 2 x 4. f ( x ) = 2 x + 2 x x 5. f ( x ) = 2 x - 2 x x 6. f ( x ) = 2 x - 2 2 x 003 10.0points Find the value of f (4) when f ( x ) = x 3 / 2 - 6 x 1 / 2 . 1. f (4) = 0 2. f (4) = 2 3. f (4) = 1 4. f (4) = 3 2 5. f (4) = 1 2 004 10.0points Find the derivative of g ( x ) = parenleftbigg x + 2 x + 3 parenrightbigg (2 x - 3) . 1. g ( x ) = x 2 - 12 x + 9 x + 3 2. g ( x ) = 2 x 2 + 12 x + 9 x + 3 3. g ( x ) = 2 x 2 + 12 x + 9 ( x + 3) 2 4. g ( x ) = x 2 + 12 x - 9 ( x + 3) 2 5. g ( x ) = 2 x 2 - 12 x - 9 ( x + 3) 2 6. g ( x ) = 2 x 2 - 12 x - 9 x + 3 005 10.0points Apply the Product Rule twice to determine the derivative of f when f ( x ) = ( x - 1)( x + 2)( x - 3) .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
qerqez (anq78) – HW08 – berg – (54595) 2 1. f ( x ) = 3 x 2 - 8 x + 1 2. f ( x ) = ( x - 1)( x + 2) 3. f ( x ) = 3 x 2 + 8 x + 1 4. f ( x ) = ( x + 2)( x - 3) 5. f ( x ) = 3 x 2 - 4 x - 5 6. f ( x ) = 3 x 2 + 4 x - 5 006 10.0points Find the derivative of F when F ( x ) = f ( x ) - 3 x f ( x ) + 3 x and f is a differentiable function. 1. F ( x ) = 6( x f ( x ) - f ( x )) ( f ( x ) + 3 x ) 2 2. F ( x ) = 3( f ( x ) + x f ( x )) f ( x ) + 3 x 3. F ( x ) = 3( f ( x ) - x f ( x )) ( f ( x ) + 3 x ) 2 4. F ( x ) = 6( f ( x ) - x f ( x )) f ( x ) + 3 x 5. F ( x ) = 6( f ( x ) - x f ( x )) ( f ( x ) + 3 x ) 2 6.
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}